2018
DOI: 10.1126/science.aao7104
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, muscle capacity, skill, and maneuvering ability in hummingbirds

Abstract: How does agility evolve? This question is challenging because natural movement has many degrees of freedom and can be influenced by multiple traits. We used computer vision to record thousands of translations, rotations, and turns from more than 200 hummingbirds from 25 species, revealing that distinct performance metrics are correlated and that species diverge in their maneuvering style. Our analysis demonstrates that the enhanced maneuverability of larger species is explained by their proportionately greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
110
1
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(119 citation statements)
references
References 57 publications
(65 reference statements)
1
110
1
7
Order By: Relevance
“…They metabolize nectar sugar rapidly and efficiently (Karasov et al 1986). Agile hovering flight (Dakin et al 2018) gives them an exceptional ability to approach and handle flowers without landing. They possess acute color vision and lack innate preference for colors ranging from near UV to long red wavelengths (Stiles 1976;Goldsmith and Goldsmith 1979;Lunau et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…They metabolize nectar sugar rapidly and efficiently (Karasov et al 1986). Agile hovering flight (Dakin et al 2018) gives them an exceptional ability to approach and handle flowers without landing. They possess acute color vision and lack innate preference for colors ranging from near UV to long red wavelengths (Stiles 1976;Goldsmith and Goldsmith 1979;Lunau et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that species with lower wing-loading also perform faster rotations and more sharp turns [29], both of which were also associated with an individual's overall unpredictability in our analysis. However, contrary to the facilitation hypothesis, we found that unpredictability was not related to burst muscle capacity, one of the most important traits that determines power generation for flying hummingbirds [28,32,44].…”
Section: Discussionmentioning
confidence: 57%
“…Next, we evaluated which morphological and muscle traits best explain an individual's overall unpredictability. Measures of body mass, wing loading, and aspect ratio were taken from the same individuals in the maneuvering trials [29]. We obtained estimates of species-average muscle capacity based on previous studies that used a transient load-lifting assay [29,32,44].…”
Section: (D) Maneuvers Morphology and Entropymentioning
confidence: 99%
See 1 more Smart Citation
“…vertical ascent are also capable of controlled high-speed shaking (Movie 3), a behavior otherwise only known during hovering in rain (Ortega-Jimenez and Dudley, 2012; this aerial shaking sequence was not included in either the data tables or power estimates). Such precise positional control during rapid ascent, as well as the vertical glide, further extend the range of novel maneuvers (see also Dakin et al, 2018) that have been recently described for this amazing lineage of birds.…”
Section: Discussionmentioning
confidence: 59%